Answer:
(-2, 3)
Step-by-step explanation:
4x + 5y = 7
3x - 2y = -12
Let's solve this by elimination. We want to eliminate one variable at a time. This means we need to multiply the equations to create a common multiple to cancel out a variable.
Let's work with y.
5y and -2y: For these values to cancel out, we need to multiply each term to create a common multiple.
2(4x + 5y = 7)
5(3x - 2y = -12)
Multiply.
8x + 10y = 14
15x - 10y = -60
Eliminate.
23x = -46
Divide both sides by 23.
x = -2
Now that we know x, let's plug it back into one of equations to find y.
4x + 5y = 7
4(-2) + 5y = 7
Multiply.
-8 + 5y = 7
Add.
5y = 15
Divide.
y = 3
Now we know x and y; let's plug both back into the equation we have not checked yet.
3x - 2y = -12
3(-2) - 2(3) = -12
Multiply.
-6 - 6 = -12
Subtract.
-12 = -12
Your solution is correct.
(-2, 3)
Hope this helps!
Answer:
Step-by-step explanation:
Correct answer is B... You can plug in values for n. Plug in 1 for n and the out put is 12. Plug in 2 for n and the output is 13.5
Top one is 56
-9 + <u>112 </u>= 7(x2 - 8x + <u>16 </u>)
I not sure but this what i think